Efikasi Dua Jenis Ekstrak Tumbuhandan Kombonasi KeduanyaTerhadap Mortalitas Hama Ulat Bawang Merah Spodoptera exiguaHubn.(LEPIDOPTERA:NOCTUIDAE) - Rifai, Hasriyanty, Burhanuddin Nasir, Muh. (AGROTEKBIS, 2016)
The study aims is todetermine the effectiveandefficient concentration ofthe twokinds of plant extraction in asingletestand thecombination of both onthe mortality of Spodopteraexiqualarvaand to determineLC50 values.The useofthis study is as informationabout thetwotypes of plantsthat workcompatible inpest controlSpodopteraexigua.The research was conducted in July through September 2014 were held at the Laboratory of Plant and PestÂ Tadulako University.The study useda completely randomized design(CRD) with 5treatments and3 replications.The treatments are: A(K1 = 0:25%), B (K2 = 0:50%),C(K3 = 0.75%),D(K4 =1.00%) andE (K5=1:25%). The variables observed arethemortality ofSpodopteraexigua.Larva Used is instar 3.The results showedthat ina singletest ofplant extracts ofSidondo Plant (Vitex negundo L) in theconcentration of 1% is aneffective concentrationwithLC50 valuesof 0.10% toobtaine 83.33% mortalityandplant extracts of âPatah Tulangâ (Euphorbia tirucalli) in concentration of1% is aneffectiveconcentration withtheLC50value of0.08% to obtaine 83.33% mortality,a combination concentration ofSidondo Plant (Vitex negundo L)extracts and âPatah Tulangâ (Euphorbia tirucalli) of 0.50% is an effective concentration with LC50 values of 0.09% on mortality of larvae of Spodoptera exigua tomortalityof 48 JSA can reach until 83.33%.